Chemical Characterization of Trichoderma spp. Extracts with Antifungal Activity against Cocoa Pathogens - Ivan Chóez-Guaranda; Fernando Espinoza-Lozano; Dennys Reyes-Araujo; Christian Romero; Patricia Manzano; Luis Galarza; Daynet Sosa (Molecules, 2023)
Ecuador is one of the major cocoa producers worldwide, but its productivity has lately been affected by diseases. Endophytic biocontrol agents have been used to minimize pathogenic effects; however, compounds produced by endophytes are minimally understood. This work presents the chemical characterization of the Trichoderma species extracts that proved inhibition against cocoa pathogens. Solid–liquid extraction was performed as a partitioning method using medium with the fungal mycelia of Trichoderma reesei (C2A), Trichoderma sp. (C3A), Trichoderma harzianum (C4A), and Trichoderma spirale (C10) in ethyl acetate individually. The extract of T. spirale (C10) exhibited the growth inhibition (32.97–47.02%) of Moniliophthora perniciosa at 10 µg/mL, while a slight stimulation of Moniliophthora roreri was shown by the extracts of T. reesei (C2A) and T. harzianum (C4A) at higher concentrations. The inhibitory activity could be related to alkaloids, lactones, quinones, flavonoids, triterpenes, and sterols, as indicated by chemical screening and antifungal compounds, such as widdrol, β-caryophyllene, tyrosol, butyl isobutyrate, sorbic acid, palmitic acid, palmitelaidic acid, linoleic acid, and oleic acid, which were identified by gas chromatography–mass spectrometry (GC-MS). The results showed that the extracts, particularly T. spirale (C10), have the potential as biocontrol agents against witches’ broom disease; however, further studies are needed to confirm their effectiveness.